2020
DOI: 10.1155/2020/7150673
|View full text |Cite
|
Sign up to set email alerts
|

Normative Values of Retinal Nerve Fibre Layer Thickness and Optic Nerve Head Parameters and Their Association with Visual Function in an African Population

Abstract: Purpose. To determine normative values of retinal nerve fibre layer thickness (RNFL) and optic nerve head (ONH) parameters and their association with routine clinical tests such as refractive error (RE), stereoacuity (SA), and contrast sensitivity (CS) in an African population. Methods. In a cross-sectional observational study, 100 normal subjects aged 20 to 78 years were evaluated using the Cirrus HD-OCT 5000 and matched with 200 glaucoma patients. Results. Average (±SD) RNFL thickness for normal subjects was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 43 publications
(75 reference statements)
0
10
1
1
Order By: Relevance
“…It is therefore imperative that a strict visual field assessment be incorporated into the pretest license requirement for the acquisition of drivers’ licenses in Ghana. The thinning of the retinal nerve fiber layer [ 46 ] as observed in this study is an indication that it is only a matter of time for those who currently have a glaucoma hemifield test that is “within normal limits” or “borderline” to lose essential peripheral vision.”…”
Section: Resultsmentioning
confidence: 96%
“…It is therefore imperative that a strict visual field assessment be incorporated into the pretest license requirement for the acquisition of drivers’ licenses in Ghana. The thinning of the retinal nerve fiber layer [ 46 ] as observed in this study is an indication that it is only a matter of time for those who currently have a glaucoma hemifield test that is “within normal limits” or “borderline” to lose essential peripheral vision.”…”
Section: Resultsmentioning
confidence: 96%
“…An Australian study found the average RNFL to be 99.4 µm using the same model Cirrus HD-OCT 4000 when examining young adults (Tariq et al 2012). The other studies using different Spectral Domain OCTs report different thicknesses varying from 90.1 to 102.4 µm (Bendschneider et al 2010;Knight et al 2012;Li et al 2020;Ocansey et al 2020). The RNFL thickness in the present study (90.9 µm) is small compared to previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…2020; Ocansey et al. 2020). The RNFL thickness in the present study (90.9 µm) is small compared to previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…The thickness of GCC and RNFL is a vital determinant of retinal health [16,22]. Equipment like scanning laser polarimeter [5], Heidelberg retinal tomogram (HRT) [10], and OCT have been utilized to study the RGC layer [9][10][11].…”
Section: Discussionmentioning
confidence: 99%